2021
DOI: 10.1021/acsomega.1c00432
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption, Gas-Sensing, and Optical Properties of Molecules on a Diazine Monolayer: A First-Principles Study

Abstract: Using first-principles calculations, the structural, electronic, and optical properties of CO 2 , CO, N 2 O, CH 4 , H 2 , N 2 , O 2 , NH 3 , acetone, and ethanol molecules adsorbed on a diazine monolayer were studied to develop the application potential of the diazine monolayer as a room-temperature gas sensor for detecting acetone, ethanol, and NH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…This specific variation in work function could enable MoSSe to serve as an Φ -type gas sensor for NO 2 , SO 2 and NO detection. 59–61 Moreover, it was shown that the physical adsorption of other gases NH 3 , HCN, CO 2 , CO, H 2 and H 2 S did not alter the work function considerably. Thus, the work function results indicated a high possibility of chemisorption of NO 2 on the Se site of the MoSSe monolayer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This specific variation in work function could enable MoSSe to serve as an Φ -type gas sensor for NO 2 , SO 2 and NO detection. 59–61 Moreover, it was shown that the physical adsorption of other gases NH 3 , HCN, CO 2 , CO, H 2 and H 2 S did not alter the work function considerably. Thus, the work function results indicated a high possibility of chemisorption of NO 2 on the Se site of the MoSSe monolayer.…”
Section: Resultsmentioning
confidence: 99%
“…This specific variation in work function could enable MoSSe to serve as an F-type gas sensor for NO 2 , SO 2 and NO detection [59][60][61]. Moreover, it was shown that the physical adsorption of other gases NH 3 , HCN, CO 2 , CO, H 2 and H 2 S did not alter the work function considerably.…”
mentioning
confidence: 94%
“…[1][2][3][4][5][6] Some of the most common polluting gases include hydrogen disulfide (H 2 S), nitrogen dioxide (NO 2 ), acetone, and ammonia (NH 3 ). [7][8][9][10] These gases have considerable health repercussions and are significant contributors to lung diseases like emphysema, respiratory irritation syndrome, and chronic obstructive pulmonary disease. [11][12][13] In particular, NO 2 is a highly toxic gas and is a major contributor to air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery in 2004, graphene has presented many fascinating properties, but its zero band-gap feature critically limits its myriad of applications in transistors, electronics, photonics, etc. Although the modification of graphene can effectively open its band gap, this also reduces the electronic quality of the material, which is impractical for device applications. This situation has stimulated scientists to design and investigate two-dimensional (2D) materials with semiconducting properties. Researchers have directed their studies to materials with layered honeycomb structures similar to that of graphite. One of the most widely studied classes of these materials is 2D transition metal disulfides (TMDs). 2D TMDs, which are nanomaterials in the formula of MX 2 , M are TM atoms, such as Mo, W, and Ge, sandwiched between two X atoms (i.e., VIA group like S, Se, and Te), are structurally similar to graphene (i.e., owning hexagonal structures), but compensate for the zero band-gap of graphene. The participation of TM d-electrons with different numbers makes 2D TMDs exhibit different electrical properties, such as semiconducting with band-gap widths of about 1–2 eV, metallic, semiconductivity, and charge density wave behaviors, and thus have attracted remarkable interest for their potential applications in field-effect transistors, gas sensors, optical sensors, lubricants, etc. …”
Section: Introductionmentioning
confidence: 99%